2000
DOI: 10.1101/gad.14.5.574
|View full text |Cite
|
Sign up to set email alerts
|

Induction of terminal differentiation by constitutive activation of p38 MAP kinase in human rhabdomyosarcoma cells

Abstract: MyoD inhibits cell proliferation and promotes muscle differentiation. A paradoxical feature of rhabdomyosarcoma (RMS), a tumor arising from muscle precursors, is the block of the differentiation program and the deregulated proliferation despite MyoD expression. A deficiency in RMS of a factor required for MyoD activity has been implicated by previous studies. We report here that p38 MAP kinase (MAPK) activation, which is essential for muscle differentiation, is deficient in RMS cells. Enforced induction of p38… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 216 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…It has previously been reported that the enforced induction of MKK6/p38 pathways restores the myogenic differentiation of ERMS cell lines ( 10 ). The present study demonstrates for the first time, to the best of our knowledge, that extracellular signals, such as those induced by the MEK/ERK inhibitor within the pathological myogenesis of ERMS, restore the activation of endogenous MKK6/p38.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It has previously been reported that the enforced induction of MKK6/p38 pathways restores the myogenic differentiation of ERMS cell lines ( 10 ). The present study demonstrates for the first time, to the best of our knowledge, that extracellular signals, such as those induced by the MEK/ERK inhibitor within the pathological myogenesis of ERMS, restore the activation of endogenous MKK6/p38.…”
Section: Discussionmentioning
confidence: 99%
“…no. 14670; Addgene, Inc.), expressing dominant negative and constitutively active MKK3 isoforms, respectively; the MKK6-EE (caMKK6-EE) constitutively active form of MKK6 was a gift from Professor Puri Pier Lorenzo (Development, Aging and Regeneration Program, Sanford Burnham Prebys Medical Discovery Institute, La Jolla, CA, USA) ( 10 ). Plasmids expressing shRNA specific for p38α knockdown and puromycin resistance for transfected cell selection were obtained from OriGene Technologies, Inc. shRNAs were cloned in the pRS plasmid under the U6 promoter, with puromycin as selectable marker and ampicillin as bacterial resistance.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The canonical activation pathway of p38 MAPK phosphorylation at the Thr180 and Tyr182 residues is essential to activate its kinase activity to either prevent or induce apoptosis [ 41 ]. The intensity of p38 MAPK activation has been linked with its pro-death or pro-survival role, whereby potent p38 MAPK activation is associated with senescence [ 42 ] and terminal cell differentiation [ 43 ]. On the other hand, normal p38 activation has a cell survival effect [ 44 ].…”
Section: Discussionmentioning
confidence: 99%